Efficacy and effectiveness of Ceftaroline Fosamil in patients with pneumonia: a systematic review and meta-analysis - Sotgiu, Giovanni (Respir Res, 2018)
BACKGROUND: Pneumonia is a relevant clinical and public health issue worldwide frequently associated with infections caused by Multi-Drug Resistant (MDR) pathogens. Ceftaroline fosamil is a promising new antibiotics with broad-spectrum bacterial activity. The aim of this systematic review and meta-analysis is to assess the efficacy and the effectiveness of ceftaroline fosamil in community-acquired (CAP), hospital-acquired (HAP), healthcare-associated (HCAP) and ventilator-associated (VAP) pneumonia. METHODS: A systematic review and meta-analysis was carried out retrieving both experimental and observational studies. RESULTS: A total of 2364 records was found and 14 manuscripts were finally considered eligible. The pooled efficacy/effectiveness was 81.2% (I(2): 1.2%) in all types of pneumonia. The pooled relative risk of clinical cure was 1.1 (I(2): 0.0%). The success rate was higher than 70% for infections caused by S. pneumoniae and S. aureus, including MDR pathogens. CONCLUSIONS: Ceftaroline fosamil showed a high efficacy/effectiveness in patients with any type of pneumonia with a good safety profile. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12931-018-0905-x) contains supplementary material, which is available to authorized users.